Consider the differential equation [tex]y - 4 y^{2} = ( y^{7}+1x)y' [/tex] where y(0)=1 Solve this equation by the following method: First, find a suitable integrating factor to obtain an implicit solution F(x,y) = C. This implicit solution cannot be solved explicitly for y but it can be solved explicitly for x.

Respuesta :

You have

[tex]\underbrace{(y-4y^2)}_M\,\mathrm dx-\underbrace{(y^7+x)}_N\,\mathrm dy=0[/tex]

with partial derivatives

[tex]M_y=1-8y[/tex]
[tex]N_x=-1[/tex]

An integrating factor in terms of [tex]y[/tex] is easy to find:

[tex]\mu(y)=\exp\left(\displaystyle\int\frac{N_x-M_y}M\,\mathrm dy\right)[/tex]
[tex]\mu(y)=\exp\left(\displaystyle\int\frac{8y-2}{y-4y^2}\,\mathrm dy\right)[/tex]
[tex]\implies\mu(y)=\dfrac1{y^2}[/tex]

Distributing [tex]\mu(y)[/tex] across the ODE gives

[tex]\underbrace{\dfrac{y-4y^2}{y^2}}_{M^*}\,\mathrm dx-\underbrace{\dfrac{y^7+x}{y^2}}_{N^*}\,\mathrm dy=0[/tex]

with partial derivatives

[tex]{M^*}_y=-\dfrac1{y^2}[/tex]
[tex]{N^*}_x=-\dfrac1{y^2}[/tex]

so the modified ODE is exact.

Now,

[tex]F_x(x,y)=M^*(x,y)[/tex]
[tex]F(x,y)=\displaystyle\int\dfrac{y-4y^2}{y^2}\,\mathrm dx[/tex]
[tex]F(x,y)=\left(\dfrac1y-4\right)x+f(y)[/tex]

[tex]F_y(x,y)=N^*(x,y)[/tex]
[tex]-\dfrac x{y^2}+f'(y)=-y^5-\dfrac x{y^2}[/tex]
[tex]f'(y)=-y^5[/tex]
[tex]\implies f(y)=-\dfrac16y^6+C[/tex]

and so the general solution is

[tex]F(x,y)=\left(\dfrac1y-4\right)x-\dfrac{y^6}6=C[/tex]

Solving explicitly for [tex]x[/tex], we have

[tex]x=\dfrac{C+\frac{y^6}6}{\frac1y-4}=\dfrac{Cy+y^7}{6-24y}[/tex]
ACCESS MORE